Dinamika HAM dalam Perbincangan Tiga Dimensi: Tinjauan Konseptual dan Praktis - Max Regus; Marianus Supar Jelahut; Antonius Nesi (Jurnal Ledalero, 2020)
Human Rights (HAM) has achieved a lot of progress as well as a stalemate. The human rights condition at these two points also shows human rights dynamics concerning various dimensional contexts. This article explicitly discusses the significant dimensions of the dynamics of human rights. Based on a critical literature review and practical reflection, this study proposes two three-dimensional analysis models of human rights dynamics at both global and national levels. The first model deals with the historical, theoretical, and practical dimensions of human rights dynamics. The second model explains the normative-philosophical, political, and sociological dimensions of the dynamics of human rights. This article consists of several sections, including an introduction, an analytical framework, the two-dimensional model of human rights dynamics, and a conclusion. Keywords: Human rights, Human rights dynamics, State, R2P, Citizen